Synthesis and Characterization of Laggera aurita-Derived KOH Activated Carbon (LAKOHAC) and Role for the Adsorption of Water-Soluble Fraction of Benzene (WSFB) in Oil-Spilled Water - Bala I. ABDULKARIM; Umar IDRISS (FUDMA Journal of Engineering and Technology, 2025)
Chronic oil spills in Nigeria’s Niger Delta have caused significant water contamination, particularly by water-soluble fraction of benzene (WSFB) a hazardous carcinogen. This research investigates the development and characterization of potassium hydroxide-activated carbon from Laggera aurita biomass (LAKOHAC) for benzene remediation. The synthesis involved carbonization followed by chemical activation with KOH, with comprehensive characterization using SEM, FTIR, BET surface area analysis, and XRD techniques. FTIR spectroscopy revealed critical functional groups (C-H, C-O, COO⁻, C=O, and O-H) that enable benzene adsorption through multiple mechanisms: π-π interactions, hydrogen bonding, electrostatic attraction, and van der Waals forces. SEM imaging showed a highly porous morphology featuring a honeycomb structure with interconnected pores, surface cracks, and fibrous elements - characteristics that enhance benzene accessibility. Surface defects and roughness provided additional high-energy adsorption sites. Elemental analysis via EDXRF identified potassium (10.66%) and sulfur (0.67%) as dominant elements, along with calcium (0.61%), phosphorus (0.11%), and chlorine (0.58%). These elements facilitate various adsorption mechanisms including cation-π interactions, thiol-mediated hydrogen bonding, and phosphate electrostatic attraction.